PENGARUH KEPRIBADIAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN PESISIR SELATAN - Zusmawati Zusmawati; Zoli Gemilang (LP2M Universitas Bina Bangsa, 2022)
The purpose of this study was to examine the effect of personality and work discipline variables on the performance of the employees of the Pesisir Selatan Education and Culture Office. Collecting data by distributing questionnaires to 59 respondents using a saturated sampling technique, where all members of the population are sampled, using multiple linear regression testing with the help of the SPSS application. The results of the study show that personality has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance